Detachment and re-attachment of Salmon lice during full-scale delousing operations on Salmon farms - Maria Guttu; Anna S. Båtnes; Arnfinn Aunsmo; Thea Bjørnland; Yngvar Olsen (Aquaculture, 2025)

The decline in sea lice numbers during freshwater treatments in salmon aquaculture - Maria Guttu; Maria Gaasø; Anna S. Båtnes; Yngvar Olsen (Aquaculture, 2024)

Planktonic and Parasitic Sea Lice Abundance on Three Commercial Salmon Farms in Norway Throughout a Production Cycle - Lone S. Jevne; Maria Guttu; Anna S. Båtnes; Yngvar Olsen; Kjell I. Reitan (Frontiers in Marine Science, 2021)
The present article reports the densities of planktonic sea lice ( Lepeophtheirus salmonis and Caligus elongatus ) in three Atlantic salmon ( Salmo salar ) localities, and the relationship between the abundance of adult sea lice on the salmon and the densities of planktonic sea lice stages, during a complete production cycle followed by a fallowing period. Samples were taken downstream inside and immediately outside of cages, at one locality with lice skirts and two localities without lice skirts. There were no differences in densities of planktonic sea lice in samples taken from the inside or the outside of cages for any of the localities. However, the proportion-non-zero of planktonic sea lice samples taken from inside the cage was higher during months with a temperature above 9°C (mean abundance: 0.40–2.5 individuals m –3 ) than months with temperature below 9°C (mean abundance: 0.02–0.21 individuals m –3 , odds ratio of the proportion-non-zero: p < 0.01). Densities of planktonic sea lice correlated most strongly with temperature in the first year (τ = 0.44–0.57, p < 0.05). A significant correlation between the number of adult female lice on salmon and average density of plankton sea lice was found in the locality with lice skirts during the second year (τ = 0.43 inside cages, τ = 0.58 outside cages, both p values < 0.05). Background levels of planktonic sea lice in the succeeding fallowing period showed neither L. salmonis nor C. elongatus planktonic sea lice, suggesting that there was successful reduction of the densities of planktonic sea lice for this area during the fallowing period.